Formation of Frost Damages in Coniferous Trees in Different Climatic Periods on the Polar Ural Mountains - M. Gurskaya A.; М. Гурская А. (Izvestiya Rossiiskoi Akademii Nauk Seriya Geograficheskaya, 2018)
Frequency of recurrence, intensity and spatio-temporal distribution of frost damage in larch and spruce growing on the same southwest exposed slope at the upper tree-line and at the bottom of the mountain valley in the Polar Ural Mountains were studied with aim to reveal the dynamics of their formation in different climatic periods over the last 100 years. At the upper tree-line damages form more often in larch than in spruce, but at the bottom of the valley, on the contrary, damages form two-three times less frequently in larch than in spruce in the same climatic periods. The high frequency of damage formation in early wood is confined with warm climatic periods with early start of vegetation and low May snow depth. The most extreme years have been identified, when a large number of trees are damaged. The difference in frequency of frost damage formation with West Siberian has shown. Risk of a damage of coniferous trees by late spring frosts due to recent climate changes in the Polar Urals is increased. В горах Полярного Урала изучены частота повторяемости, интенсивность и пространственно-временное распределение морозобойных повреждений у ели и лиственницы, произрастающих в пределах одного склона юго-западной экспозиции на верхней границе распространения деревьев и на дне горной долины, с целью выявить пространственно-временную динамику их формирования в различные климатические периоды за последние 100 лет. На верхней границе леса повреждения формируются чаще у лиственницы по сравнению с елью, а на дне горной долины у лиственницы, напротив, повреждения формируются в два-три раза реже, чем у ели в одни и те же климатические периоды. Высокая частота формирования повреждений в ранней древесине хвойных приурочена к теплым климатическим периодам с ранним началом вегетации и небольшой высотой снега в мае. Выявлены наиболее экстремальные годы, когда повреждается большое количество деревьев, показано отличие от местообитаний, расположенных в Западной Сибири. Существует повышенный риск повреждений хвойных деревьев поздними весенними заморозками в связи с недавними изменениями климата на Полярном Урале.